Government management on food service industry and the intention to practice standard operating measures during COVID-19 / Wang Xiaohui - Wang, Xiaohui (2021)
The COVID-19 global pandemic has changed the relationship between consumers and food, increased the frequency of cooking at home, and adopted strict precautions when shopping, delivering meals and eating out. This time, we took the form of an online questionnaire survey, which led and received effective responses from 200 interviewees. Use descriptive statistics to analyze data and use SPSS data processing methods to pass reliability analysis, validity analysis, factor analysis, and correlation analysis, the average score of food safety knowledge of Malaysian respondents is 8.92 (11 .00 = highest score), indicating that consumers have a high level of food safety knowledge and sufficient knowledge reserves, which can effectively prevent COVID-19 infection. The Alpha coefficient is 0.882, the test KMO=0.700 (KMO>0.7), Sig.<0.001, and the total variance explanation chart, we explored the relationship between the two variables (health and safety knowledge and people’s attitude/behavior ability to respond to the epidemic) The correlation, the result (sig = 0.796), shows that the relationship between the two is to play a positive role, the higher people's health and safety knowledge. During the COVID-19 period, regarding Malaysia and China’s safety policies for the catering service industry, in terms of the effectiveness of epidemic prevention, the containment strategy adopted by China is more effective in terms of epidemic control.